Efektivitas Pelatihan Positive Parenting Terhadap Penurunan Kecenderungan Perilaku Kekerasan Orang Tua Pada Anak di Kota Makassar - Ismi Shahriani Silmi; Muh. Daud; Nur Afni Indahari (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Violence against children is all forms of hurtful behavior physically and mentally carried out by parents to children. This study aims to determine the effectiveness of positive parenting training on decreasing behavioral tendencies parental violence against children in the city of Makassar. The subjects in this study amounted to 6 parents who have children aged 0-12 years. This study used a quasi-experimental one group pretest posttest design. This study uses a scale of tendencies toward violent behavior in children with a reliability value of 0.849. The results showed that positive parenting training was not effective in reducing the tendency to violence in children, based on the significant value between pretest and posttest (W=2.5 p=0.212). Positive parenting training is not proven to have a significant effect in increasing the knowledge of parents who have a tendency to violent behavior in children. Based on the results, the value (mean=4.67) in the pretest is smaller than the value (mean=5) in the posttest so that there is an increase in the mean of knowledge. This research contributes to parents in order to help them understand positive parenting so that they can achieve parenting goals.